If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -2(-1x + -6) = -37 Reorder the terms: 5x + -2(-6 + -1x) = -37 5x + (-6 * -2 + -1x * -2) = -37 5x + (12 + 2x) = -37 Reorder the terms: 12 + 5x + 2x = -37 Combine like terms: 5x + 2x = 7x 12 + 7x = -37 Solving 12 + 7x = -37 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 7x = -37 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = -37 + -12 7x = -37 + -12 Combine like terms: -37 + -12 = -49 7x = -49 Divide each side by '7'. x = -7 Simplifying x = -7
| x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 | | -6.47-10.16= | | 4x^2+3=-18x | | +0-(+12)= | | ((5)/(2x+4)+4)=((-1)/(x+2)) | | 1=x+23 | | 6x+3=x-6 | | 5y+2(y-4)=5(y+1)-2 | | 4(y+1)+5=(y-1)+y | | -3x-6y=17 |